2019
DOI: 10.1111/jace.16531
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study on frictional dependence and predictive accuracy of viscoelastic model for optical glass using compression creep test

Abstract: Compression creep tests (CCTs) have been widely used in phenomenological characterization of viscoelastic materials such as glasses. However, disturbed by specimen‐tool interface friction, the real stress‐strain data regarding the pure viscoelastic deformation are frequently misestimated in conventional CCTs, causing decreased accuracies of the derived viscoelastic parameters. This study proposes a comprehensive CCT‐based approach to develop a viscoelastic model with weakened frictional disturbance and enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
(118 reference statements)
1
15
0
Order By: Relevance
“…While two data have a good match within the first relaxation response, ie, fast relaxation time ( τ 1 ≈10 −5 − 10 −2 seconds), an obvious distinction can be recognized when one looks a bit closer on the long‐term relaxation response ( τ 2 ≈10 −2 – 10 3 seconds) as indicated in the zoomed plot (Figure B). Similar findings can be seen in the work of Zhou et al and Yu et al; however, impacts of such nonidentical relaxation response in the long term on the creep displacements have not been studied. It is obvious that the first relaxation period occurs extremely short (<0.01 second) compared to the total pressing time.…”
Section: Conventional Characterization Of Thermo‐viscoelastic Materiasupporting
confidence: 83%
See 4 more Smart Citations
“…While two data have a good match within the first relaxation response, ie, fast relaxation time ( τ 1 ≈10 −5 − 10 −2 seconds), an obvious distinction can be recognized when one looks a bit closer on the long‐term relaxation response ( τ 2 ≈10 −2 – 10 3 seconds) as indicated in the zoomed plot (Figure B). Similar findings can be seen in the work of Zhou et al and Yu et al; however, impacts of such nonidentical relaxation response in the long term on the creep displacements have not been studied. It is obvious that the first relaxation period occurs extremely short (<0.01 second) compared to the total pressing time.…”
Section: Conventional Characterization Of Thermo‐viscoelastic Materiasupporting
confidence: 83%
“…It is demonstrated that the accuracy of the obtained viscoelastic parameters can be enhanced if the friction between the glass and mold is sufficiently small, 23 as approached in this research, or the error due to the friction can be dismissed from the displacement data. 28 The authors agree that the friction at the glass-mold interface, which cannot be avoided by the compression setup, may violate the pure creep deformation due to viscoelastic property of an investigating material. In this study, however, another reason that crucially results in the disagreement between the experiment and simulation results is elucidated.…”
Section: Numerical Verification Of Shear Relaxation Parametersmentioning
confidence: 84%
See 3 more Smart Citations